Investigation On Physical, Thermal, Mechanical And Morphological Properties Of Kenaf Reinforced Recycled Polypropylene/Polyethylene Composites - Jumadi, Muhammad Taufiq (2019)
The recycled plastic extracted from rejected-unused disposable diapers (RUDD), which contains thermoplastic polymer such as polypropylene (PP) and polyethylene (PE) has potential to be used as natural fibre composite matrix. However, the knowledge of producing natural fibre composite (NFC) by using recycled plastic derived from RUDD and natural fibre is still limited in publication. Therefore, this research was conducted to study the physical, thermal, mechanical, and morphological properties of kenaf fibre reinforced recycled PP/PE (r-PP/PE) that derived from RUDD. The first objective was to identify the optimum processing temperature of composite using recycled plastic (r-PP/PE). The second objective was to evaluate the differences between recycled (r-PP/PE) and virgin (v-PP/PE) blends with regards to their thermal, mechanical, and morphological properties. The third objective was to study the effect of kenaf fibre loadings (0, 30, 40, 50, and 60 wt.%) on the physical (density, and water absorptivity), thermal (melting point), mechanical (hardness, tensile, flexural, and impact strength), and morphological properties of NFC. The final objective was to characterize the influence of water absorptivity on the NFC mechanical and morphological properties. Test results showed the maximum tensile properties for r-PP/PE blend was obtained at processing temperature of 180 °C. Thermal examination on r-PP/PE and v-PP/PE showed immiscibility between PP and PE elements in both blends. In addition, the degree of crystallinity and homogeneity were lower for r-PP/PE as compared to v-PP/PE, which resulted in lower mechanical properties for r-PP/PE. Furthermore, the increment of kenaf fibre loadings into r-PP/PE increased the specific density, water absorptivity, and thickness swelling properties of the composites without significant change on the melting temperature. Meanwhile, the optimum values for hardness, tensile strength, flexural strength, tensile modulus, and flexural modulus of kenaf reinforced r-PP/PE were obtained at fibre loading of 50 wt.%, 30 wt.%, 60 wt.%, 40 wt.% and 60 wt.%, respectively. Higher kenaf fibre loadings also reduced the composites impact strength. The conducted morphological analysis also revealed the occurrence of failure modes, which were due to poor fibre-matrix interfacial adhesion that causing fibre pull-out and void formation. Apart from that, the fibre breakage and matrix cracking were also observed. Finally, it was also found that water absorptivity reduced the kenaf reinforced r-PP/PE composites tensile and flexural properties. However, water absorptivity improved the composites impact strength. In conclusion, kenaf reinforced r-PP/PE composites derived from RUDD showed tremendous potential to be applied for practical applications.